Global justice, Christology and Christian ethics - Cahill, Lisa Sowle (United kingdom: Cambridge University press, 2013)
"Global realities of human inequality, poverty, violence and ecological destruction call for a twenty-first-century Christian response which links cross-cultural and interreligious cooperation for change to the Gospel. This book demonstrates why just action is necessarily a criterion of authentic Christian theology, and gives grounds for Christian hope that change in violent structures is really possible. Lisa Sowle Cahill argues that theology and biblical interpretation are already embedded in and indebted to ethical-political practices and choices. Within this ecumenical study, she explores the use of the historical Jesus in constructive theology; the merits of Word and Spirit Christologies; the importance of liberation and feminist theologies as well as theologies from the global south; and also the possibility of qualified moral universalism. The book will be of great interest to all students of theology, religious ethics and politics, and biblical studies"--
Machine generated contents note: Preface; 1. The politics of salvation; 2. Creation and evil; 3. Kingdom of God; 4. Christ; 5. Spirit; 6. Cross; 7. Nature; 8. Hope; Index
Includes bibliographical references and index.
Keywords: Jesus Christ -- Person and offices; Bible -- Theology; Christianity and justice; Globalization -- Religious aspects -- Christianity; Christian ethics